Medication Adherence in a Nationwide Cohort of Veterans Initiating Pre-exposure Prophylaxis (PrEP) to Prevent HIV Infection. (1st March 2018) - van Epps, Puja; Maier, Marissa; Lund, Brian; Howren, Matthew Bryant; Beck, Brice; Beste, Lauren; Skolnik, Avy; Vaughan-Sarrazin, Mary; Ohl, Michael E.
Abstract : Background: Current guidelines for pre-exposure prophylaxis (PrEP) to prevent HIV infection call for long-term, daily use of tenofovir disoproxil fumarate/emtricitabine (TDF/FTC). Little is known about long-term adherence with TDF/FTC prescribed for PrEP in routine clinical practice. Setting: Veterans Health Administration (VHA) clinics. Methods: We used VHA data to create a nationwide cohort of Veterans initiating PrEP between July 1, 2012, and June 30, 2016. We examined pharmacy refill data to estimate adherence based on the proportion of days covered (PDC) by TDF/FTC in the first year and used logistic regression to identify patient characteristics associated with high adherence (ie, PDC >0.8). We also quantified how often Veterans discontinued PrEP in the first year, based on a gap of 120 days or more in medication possession. Results: Among 1086 individuals initiating PrEP, the median PDC for TDF/FTC in the first year was 0.74 (interquartile range 0.40–0.92). In multivariable analysis, high adherence was associated with older age (odds ratio 1.97; 1.41–2.74 for age 50–64 compared with <35), white compared with black race (odds ratio 2.12; 1.53–2.93), and male sex (odds ratio 3.39; 1.37–8.42). Forty-four percent discontinued PrEP in the first year. Conclusions: First-year adherence with TDF/FTC was overall high in a nationwide cohort of PrEP users. Differences in adherence by age, race, and sex suggest potential for disparities in PrEP effectiveness in routine clinical practice. Abstract : Supplemental Digital Content is Available in the Text.